Development of Muslim Adventure Educational Game for Islamic Religious Education in Primary Schools - Maulana Jamaludin, Gilang; Nahriyah, Syafa'atun; Purnama Sari, Devi (TA`DIBUNA, 2025)
The development of digital technology demands innovation in interactive learning media that are in line with the characteristics of the digital native generation. In Islamic Religious Education (PAI) learning in elementary schools, the use of conventional methods such as lectures and textbooks is still dominant, thus reducing student motivation and engagement. This study aims to develop a Muslim Adventure Educational Game as an innovative and engaging PAI learning medium. The research method uses research and development (R&D) with the ADDIE model. The research subjects involved 30 fifth-grade elementary school students in Majalengka Regency, who were tested through one-to-one, small group, and large-scale trials. Data were collected through needs questionnaires, validation by material experts, media, language, and student responses. The results showed that the game was categorized as very feasible with an average expert validation score of 4.55 and student responses of 4.15. These findings confirm that the integration of Islamic values in educational games can increase student interest and engagement in PAI learning.